Work Safety Culture to Fertilizer Bagging Workers - Az-Zahra, Qurratul A'yun; Denny, Hanifa Maher; Setyaningsih, Yuliani (Universitas Mercu Buana, 2025)
Objectives: The performance of a company can be seen from the quality of the workforce in carrying out company activities. In Indonesia there are still many work accidents. In 2020, the Fertilizer Bagging Unit experienced a decrease in the number of accidents, but in 2022 there were fatal work accidents. Even though Government Regulation Number 50 of 2012 has been stipulated, there are still gaps in the field, such as work accidents caused by workers carrying out their work in an unsafe manner, not following the SOPs that have been set, and not using personal protective equipment so that the work culture does not run well. So this research is important to reduce the number of work accidents, and can identify the main factors that cause accidents that occur in the work environment of the Semarang city fertilizer bagging unit.Methodology: This research design uses cross sectional with a quantitative approach. The research location was carried out in the work area of the Fertilizer Bagging Unit of Tanjung Emas Port Semarang. The research time was conducted in June - July. Sampling in this study used purposive sampling, so that the number of samples used was 150. Data processing uses editing, coding, data entry and cleaning. Data analysis using Univariate, bivariate and Multivariate. The test used used Chi Square Test and Logistic Regression.Finding: The research results show that the most significant factor in the work safety culture of fertilizer bagging workers is safety performance with an OR value of 2.210.Conclusion: Factors associated with the implementation of work safety culture are skills, communication, worker participation and safety performance. Company recommendations are expected to implement a reward and punishment system for workers who work not in accordance with regulations and it is hoped that the company will implement an internal and external audit system to evaluate the effectiveness of safety policies.